2011
DOI: 10.1038/gt.2010.179
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and stable transduction of dopaminergic neurons in rat substantia nigra by rAAV 2/1, 2/2, 2/5, 2/6.2, 2/7, 2/8 and 2/9

Abstract: Dysfunction of the nigrostriatal system is the major cause of Parkinson's disease (PD). This brain region is therefore an important target for gene delivery aiming at disease modeling and gene therapy. Recombinant adeno-associated viral (rAAV) vectors have been developed as efficient vehicles for gene transfer into the central nervous system. Recently, several serotypes have been described, with varying tropism for brain transduction. In light of the further development of a viral vector-mediated rat model for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(75 citation statements)
references
References 55 publications
2
73
0
Order By: Relevance
“…Other studies with injections in the SN of rats reported higher transduced brain volumes using rAAV2/7, rAAV2/9, and rAAV2/1 than with rAAV2/8 and rAAV2/5, indicating species-dependent transduction efficiencies of the viral vectors. 30,33,62 In our study, the rAAV2/1-CaMKIIα0. 4 showed efficient transduction at the injection site but the transgene expression pattern was limited to about 1.2 × 1.0 mm 2 .…”
Section: Transduction Efficiencies Are Serotype Dependentmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies with injections in the SN of rats reported higher transduced brain volumes using rAAV2/7, rAAV2/9, and rAAV2/1 than with rAAV2/8 and rAAV2/5, indicating species-dependent transduction efficiencies of the viral vectors. 30,33,62 In our study, the rAAV2/1-CaMKIIα0. 4 showed efficient transduction at the injection site but the transgene expression pattern was limited to about 1.2 × 1.0 mm 2 .…”
Section: Transduction Efficiencies Are Serotype Dependentmentioning
confidence: 99%
“…About 100 ng of genomic DNA was used for the determination of the rAAV genomic copies using a real-time PCR, as described earlier. 33 Each dilution of the viral vectors was used three times and this experiment was done in two different assays.…”
Section: Vector Constructsmentioning
confidence: 99%
See 1 more Smart Citation
“…To obtain efficient gene transfer, we applied viral vector technology, engineering a hP2X7R reporter system using HIV-based lentiviral vectors (LVs) for validation in cell culture settings, and recombinant adeno-associated viral (rAAV) vectors in the brain in vivo (19). JNJ-54173717 (20,21), which has nanomolar affinity for rat P2X7R and hP2X7R, was radiolabeled with 11 C and evaluated in this rat model using small-animal PET.…”
mentioning
confidence: 99%
“…This is the case for gene therapy approaches in epilepsy, multiple sclerosis, Alzheimer disease, diabetes, Parkinson's disease, chronic pain, lysosomal storage disorders, amyotrophic lateral sclerosis, brain ischemia, seizure, Huntington disease, and others. HSV vectors have also been used for some of these indications, but currently, they have been frequently applied for gene therapy approaches in brain tumors, as is the case for adenovirus vectors as well (Maingay et al, 2005;Wong et al, 2006;Robinson et al, 2007;Lowery et al, 2009;Shih et al, 2009;Björklund et al, 2010;Manfredsson & Mandel, 2010;Eskenazi & Neumaier, 2011;Jacobs & Wang, 2011;Van der Perren et al, 2011;Vande Velde et al, 2011;Thaci et al, 2011).…”
Section: Brain Gene Therapymentioning
confidence: 99%